APPLICATION OF GAME THEORY IN THE FOOTBALL DUELS BETWEEN TWO PLAYERS INVOLVED - Amelia, Faustina
Football is a popular sport that aims to score as many goals as possible against the opponent’s goal. One of the inevitable things in football is a duel, which occurs between two or more players. The player who chooses the right action and has more power than his opponent can potentially win the duel. Winners of duels in football are very appealing to review and analyze further, considering that many factors influence the results of duels. This final assignment aims to construct a football duel between two players by applying game theory. The research method used to achieve this goal is a descriptive and comparative method with a quantitative approach so that the construction of football duels can be done using game theory. The data collection technique applied in this research involves using existing secondary data from certain sources. The results of the research show the construction of a football duel from a static game point of view, the construction of a football duel from a dynamic game point of view, and the prediction of the winner of a duel from a static and dynamic game point of view. This research concludes that the construction of a football duel from a static and dynamic game perspective can be carried out, but there are still relatively many assumptions used to simplify the problem. Games can be built according to game theory, adapting various variations in duels that actually occur in football.